2015
DOI: 10.1039/c4pp00463a
|View full text |Cite
|
Sign up to set email alerts
|

A safety study of a novel photosensitizer, sinoporphyrin sodium, for photodynamic therapy in Beagle dogs

Abstract: Sinoporphyrin sodium (DVDMS) is a novel hematoporphyrin-like photosensitizer developed for photodynamic therapy (PDT), an effective therapeutic modality for tumor treatment; however, the safety of photosensitizer-based PDT is always of great concern. The purpose of the current study was to investigate the potential repeated-dose toxicity and describe the toxicokinetic process of DVDMS-based PDT in Beagle dogs. The dogs were randomly allocated to six groups, and then were administrated a DVDMS preparation intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…PS for PDT may elicit intrinsic adverse reactions, may employ drug formulations with some toxicity, or may show toxicity as a consequence of the illumination protocol. This last concern is specific of PDT and requires the design of safety evaluation strategies that take into consideration the combination of drug and light [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…PS for PDT may elicit intrinsic adverse reactions, may employ drug formulations with some toxicity, or may show toxicity as a consequence of the illumination protocol. This last concern is specific of PDT and requires the design of safety evaluation strategies that take into consideration the combination of drug and light [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The death of mice was verified as follows: The breath, heartbeat and circulation were permanently stopped and the onset of rigor mortis was confirmed. According to previous studies, the maximum concentration of DVDMS in tumors occurs at 24 h after intravenous injection through the tail vein (10,11). Therefore, PDT and SDT were performed at this time in the present study (Fig.…”
Section: Dvdms-mediated Pdt and Sdt Inhibit Tumor Development In U-11mentioning
confidence: 88%
“…Previous studies have revealed that DVDMS has good water solubility and stability, is widely applicable in PDT and SDT, and shows good therapeutic effects against tumors, bacteria and skin diseases (11,39). Preclinical safety evaluation showed that DVDMS as a good safety profile in SD rats and beagles (10,40). Furthermore, there are two registered phase I clinical trials investigating DVDMS for the treatment of esophageal cancer and advanced solid tumors (no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 It is quite surprising, however, that very little is known about the systemic toxicities of the parent metal complexes (metalloporphyrins). 3334 One likely explanation is that many of them undergo demetallation under biological conditions. 3536…”
Section: Introductionmentioning
confidence: 99%